Numerical Study Of Heat Transfer In Cooling Passages Of Turbine Blade - Ahmed F. Khudheyer; Hussein T. Dhaiban (Journal of Engineering, 2023)
As the temperature of combustion gases is higher than the melting temperature of the turbine materials, cooling of turbine parts in a gas turbine engine is necessary for safe operation. Cooling methods investigated in this computational study included cooling flow losses. Film-cooling is one typically used cooling method whereby coolant is supplied through holes passage, in present study the holes placed along the camber line of the blade. The subject of this paper is to evaluate the heat transfer that occur on the holes of blade through different blowing coolant rates. The cases of this study were performed in a low speed wind tunnel with two tip gap at small and large (0.03 and 0.09cm) and multiple coolant flow rates through the film-cooling holes. The blowing ratios was studied whereby coolant was injected from holes placed along the tip of a large scale blade model with Reynolds number (2.1 x 105 ) of the engine was matched. Results showed that baseline Nusselt numbers on the holes were reduced along the holes passage, and heat transfer coefficient is high values at iterance region. Overall, the cooling by holes appears to be a feasible method for prolonging blade life.